The Artist and Her Muse: From Female Bodies towards Female Identities (Drakulić, Bašić, Hasanbegović, Bastašić) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper approaches artistic self-concepts from the perspective of twenty-first-century female writers. Against the background of ancient and modern constellations of the artist and the muse, one main question will concern feminist strategies of coping with this ideal union that has been shaped within a patriarchal tradition of art production for centuries. Slavenka Drakulić, Adisa Bašić, Dijala Hasanbegović, and Lana Bastašić use a variety of subversive strategies to challenge and transform the given constellation. Analysing the difficulties an emancipated modern muse faces when attempting to be recognised as an independent artist is only one possible first step to open this discussion. More active measures proposed in the selected literary examples are to reverse traditional gender roles in love relationships and to discredit male profiteers throughout the literary scene. The usefulness of such an approach shall also be discussed, considering that the ideal relationship between a muse and an artist as one of inspiration and creation must not be destroyed.
Keywords: female identities; artistic self-concepts; concepts of the muse; subversive writing